The Application of Inclusive Accounting to Improve Access to Financial Information for Retail Investors - Wendy, Wendy (PT. Hafasy Dwi Nawasena, 2025)
The significant growth in the number of retail investors in Indonesia's capital market in recent years indicates increased public participation in investment activities. However, the reality on the ground shows that retail investors still face barriers in understanding and accessing relevant financial information. Financial reports prepared with technical terms and complex formats tend to only be optimally utilized by institutional investors, resulting in information gaps that have an impact on inequality in investment decision making. This study aims to analyze the needs and challenges of retail investors in understanding financial information and explore the urgency of implementing inclusive accounting as a solution. The research uses a qualitative approach with a case study method, involving in-depth interviews with a number of active retail investors in the capital market.The research shows that retail investors have difficulty in understanding financial terminology such as EBITDA, liabilities and operating cash flows. In addition, access to official, real-time financial information is limited, with most informants relying on social media or securities apps as their main source of information. The informants expressed a preference for visual, summarized and narrative presentation of information that is easier to understand. The conclusion of this study suggests that inclusive accounting can be a strategic approach to bridge the financial literacy gap between market participants. It is expected that the implementation of inclusive accounting by companies and the support of regulators can improve information disclosure, expand access, and strengthen retail investor participation in the Indonesian capital market